The Macau Manifesto – Learning From The Development Of Cooperatives (The Macau Ricci Institute Journal, 2023)
The Macau Manifesto addresses several important issues that could significantly contribute to human well-being. Some of them are well known and part of economic common sense. “Wellbeing for All” (headline of the Manifesto’s section 2) is the foremost goal of welfare economics, the normative nucleus of modern economics, and there should be no dissenting view on this goal. The Manifesto’s suggestions for action such as the development of technologies to advance people’s well-being or the promotion of education to empower people and allow them to develop their capabilities are well-known results from traditional economic theory and empirics. Moreover, the Manifesto’s emphasis of subsidiarity is well-based in fiscal federalism. Therefore, at least for these topics there is no “new economic paradigm” in the Manifesto.